Effects of high-dose vitamin D supplementation and physical exercise on vitamin D metabolites in professional football players: A pilot study - Ksiazek, A.; Zagrodna, A.; Kowalski, K. (Nutrients, 2025)
Background/Objectives: Vitamin D plays an important role in muscle metabolism and recovery, yet its kinetics during and after football-specific physical activity remain poorly understood. Therefore, this study aimed to determine whether physical effort during a football match influences the concentration of vitamin D metabolites and to explore the effect of a single high-dose cholecalciferol supplementation combined with physical exercise on the levels of vitamin D metabolites in professional football players.